2018
DOI: 10.1002/jcla.22726
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0000467 promotes cancer progression and serves as a diagnostic and prognostic biomarker for gastric cancer

Abstract: Background Emerging evidence indicates that dysregulation of circular RNAs (circRNAs) is implicated in the development of malignancies. However, the diagnostic value and functional role of circRNAs in gastric cancer (GC) remain largely elusive. Methods Quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was performed to detect the expression of hsa_circ_0000467 in tissues, cell lines, and plasma. A receiver operating characteristic (ROC) curve was constructed to estimate the diagnostic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 31 publications
0
58
0
Order By: Relevance
“…Among the included publications, a total of 43 articles on 64 studies were analyzed involving 10,123 subjects in Table . Of the 64 studies, five studies focused on colorectal cancer (Ji et al, ; Wang, Li, et al, ; Wang et al, ; Zhang, Yang, et al, ; Zhuo, Lin, Chen, Huang, & Hu, ), 10 on breast cancer (Lu et al, ; Yin et al, ), 22 on gastric cancer (Chen, Li, Zhao, Xiao, & Guo, ; Huang, He, Liang, Huang, & Zhu, ; Li, et al, , ; Li, Shao, et al, ; Li, Song, et al, ; Lu et al, ; Lu, Shao, Ye, Xiao, & Guo, ; Shao, Chen, et al, ; Shao, Li, et al, ; Shao, Yang, et al, ; Sun, Tang, et al, ; Tian, Chen, Li, & Xiao, ; Wei et al, ; Xie et al, ; Zhao, Chen, Li, Xiao, & Zhang, ), four on lung cancer (Li, Wang, Chen, Chen, & Jin, ; Zhu et al, ; Zong et al, ), 16 on hepatocellular carcinoma (Chen, Zhang, Lin, Song, & Wang, ; Fu et al, , ; Li et al, ; Qin et al, ; Shang et al, ; Yao et al, ; Yao et al, ; Zhang, Zhang, Lin, & Wang, ; Zhang, Zhou, et al, ; Zhang, Xu, et al, ) and seven on other cancers (Fan, Cao, Liu, Zhang, & Li, ; Lan et al, ; Li et al, ; Sun, Li, et al, ; Teng et al, ; Wang, Xue, et al, ; Yang et al, ). Moreover, three articles with 13 studies explored the diagnostic value of the combined circRNAs (Chen, Li, Zhao, et al, ; Fan et al, ; Li, Shao, et al, ) in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included publications, a total of 43 articles on 64 studies were analyzed involving 10,123 subjects in Table . Of the 64 studies, five studies focused on colorectal cancer (Ji et al, ; Wang, Li, et al, ; Wang et al, ; Zhang, Yang, et al, ; Zhuo, Lin, Chen, Huang, & Hu, ), 10 on breast cancer (Lu et al, ; Yin et al, ), 22 on gastric cancer (Chen, Li, Zhao, Xiao, & Guo, ; Huang, He, Liang, Huang, & Zhu, ; Li, et al, , ; Li, Shao, et al, ; Li, Song, et al, ; Lu et al, ; Lu, Shao, Ye, Xiao, & Guo, ; Shao, Chen, et al, ; Shao, Li, et al, ; Shao, Yang, et al, ; Sun, Tang, et al, ; Tian, Chen, Li, & Xiao, ; Wei et al, ; Xie et al, ; Zhao, Chen, Li, Xiao, & Zhang, ), four on lung cancer (Li, Wang, Chen, Chen, & Jin, ; Zhu et al, ; Zong et al, ), 16 on hepatocellular carcinoma (Chen, Zhang, Lin, Song, & Wang, ; Fu et al, , ; Li et al, ; Qin et al, ; Shang et al, ; Yao et al, ; Yao et al, ; Zhang, Zhang, Lin, & Wang, ; Zhang, Zhou, et al, ; Zhang, Xu, et al, ) and seven on other cancers (Fan, Cao, Liu, Zhang, & Li, ; Lan et al, ; Li et al, ; Sun, Li, et al, ; Teng et al, ; Wang, Xue, et al, ; Yang et al, ). Moreover, three articles with 13 studies explored the diagnostic value of the combined circRNAs (Chen, Li, Zhao, et al, ; Fan et al, ; Li, Shao, et al, ) in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Among the included publications, a total of 43 articles on 64 studies were analyzed involving 10,123 subjects in Table S1. Of the 64 studies, five studies focused on colorectal cancer (Ji et al, 2018;Wang, Li, et al, 2018;Wang et al, 2015;Zhang, Yang, et al, 2018;Zhuo, Lin, Chen, Huang, & Hu, 2017), 10 on breast cancer Yin et al, 2018), 22 on gastric cancer (Chen, Li, Zhao, Xiao, & Guo, 2017;Huang, He, Liang, Huang, & Zhu, 2017;Li, Shao, et al, 2018;Li, Song, et al, 2017;Lu et al, 2018;Shao, Chen, et al, 2017;Shao, Li, et al, 2017;Sun, Tang, et al, 2018;Tian, Chen, Li, & Xiao, 2018;Wei et al, 2019;Xie et al, 2018;Zhao, Chen, Li, Xiao, & Zhang, F I G U R E 1 The flow diagram of this meta-analysis 2018), four on lung cancer (Li, Wang, Chen, Chen, & Jin, 2018;Zhu et al, 2017;Zong et al, 2018), 16 on hepatocellular carcinoma (Chen, Zhang, Lin, Song, & Wang, 2018;Fu et al, 2018Fu et al, , 2017Li et al, 2019;Qin et al, 2016;Shang et al, 2016;Yao et al, 2017;Yao et al, 2018;Zhang, Zhou, et al, 2018; and seven on other cancers (Fan, Cao, Liu, Zhang, & Li, 2019;Lan et al, 2018;Li et al, 2019;Sun, Li, et al, 2018;…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The detection of piRNA-1245 in GJ could be a new avenue for differentiating GC from healthy people. [24][25][26][27][28][29] Some altered ncRNAs played a crucial role in the regulation of malignant phenotypes of tumor. 24 Mo et al elucidated that lncRNA RP11-555H23.1 showed an important role in the occurrence of GC, and used as a new marker of GC.…”
Section: Accumulating Literatures Showed That Alternation Of Non-codingmentioning
confidence: 99%
“…On a global scale, a recent study showed that the 5‐year survival rate of stage I patients can be more than 90%, while that of the stage IV patients who already show distant metastases is only approximately 18% . Yet, traditional serum tumor biomarkers such as carcinoembryonic antigen (CEA), carbohydrate antigen 19‐9(CA19‐9), and carbohydrate antigen 72‐4 (CA72‐4) are not very effective in the diagnosis of GC . Their sensitivity and specificity are relatively low .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Yet, traditional serum tumor biomarkers such as carcinoembryonic antigen (CEA), carbohydrate antigen 19-9(CA19-9), and carbohydrate antigen 72-4 (CA72-4) are not very effective in the diagnosis of GC. 7,8 Their sensitivity and specificity are relatively low. 9 Therefore, it is necessary to search for stable, non-invasive, and cost-effective biomarkers to improve the diagnosis and monitoring patients with GC.…”
Section: Introductionmentioning
confidence: 99%